Imatinib Mesylate–Induced Pseudoporphyria in Two Children. Issue 5 (12th June 2014) - Mahon, Caroline; Purvis, Diana; Laughton, Stephen; Bradbeer, Peter; Teague, Lochie
Abstract Imatinib mesylate was the first of several tyrosine kinase inhibitors approved for use in the treatment of a number of human cancers. Adverse cutaneous reactions to imatinib are common. Pseudoporphyria has been infrequently reported in adults undergoing imatinib therapy for chronic myeloid leukemia. We present two children with pseudoporphyria induced by imatinib therapy for hematologic malignancies. In view of the burgeoning use of imatinib in children, physicians should be aware that pseudoporphyria may develop as a consequence of imatinib therapy.